PENGEMBANGAN BAHAN AJAR FLIPBOOK MATA PELAJARAN BAHASA INDONESIA MATERI KATA SIFAT UNTUK SISWA KELAS V DI SD NEGERI 5 NONGAN - Ni Luh Ketut Jenutri Sari Devi; I Wayan Numertayasa (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This research focuses on the development of a flipbook teaching material for the Bahasa Indonesia subject, specifically on the topic of adjectives, for fifth-grade students at SD Negeri 5 Nongan. This study employs a Research and Development (R&D) approach using the ADDIE model and was conducted at SD Negeri 5 Nongan. The research subjects consisted of two experts: one validating the material aspect and the other validating the design aspect. Data collection techniques included questionnaires and interviews, while data analysis was conducted using descriptive statistical analysis. The results of the study indicate that the flipbook teaching material for the Bahasa Indonesia subject on the topic of adjectives is appropriate for use in fifth-grade learning at SD Negeri 5 Nongan. This is evidenced by the material expert validation results, which obtained a score of 60 with an average validity rate of 80%, categorized as “Highly Valid.” Meanwhile, the design expert validation results obtained a score of 62 with an average validity rate of 82.6%, also categorized as “Highly Valid.” Therefore, this flipbook teaching material is expected to enhance students’ engagement, understanding, and learning motivation in Bahasa Indonesia instruction in the digital era.